2014
DOI: 10.1097/bpb.0000000000000052
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of semirigid hip orthosis in the delayed treatment of developmental dysplasia of the hip

Abstract: Level IV. Case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…As expected, Grades 1 and 2 were successfully reduced, which is consistent with our previous study based on a synthetic model (Ardila et al, 2013) as well as from clinical observation (Uras et al, 2014). Grade 3 was successfully reduced while Grade 4 dislocation was not.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As expected, Grades 1 and 2 were successfully reduced, which is consistent with our previous study based on a synthetic model (Ardila et al, 2013) as well as from clinical observation (Uras et al, 2014). Grade 3 was successfully reduced while Grade 4 dislocation was not.…”
Section: Discussionsupporting
confidence: 91%
“…Results provide insight of their contribution to reduction of DDH on severe Grade 3 and 4 dislocations whenever the PH is used and gravity is acting. It is known from clinical observation that reduction is successful whenever the PH is used on Grades 1 and 2 (Uras et al, 2014), thus these two grades were analyzed but values are not reported. Force and moment contribution of the adductor muscles while the PH is being used are reported for Grade 3 and Grade 4 (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 28 However, the PH is relatively complex to use and the reduced compliance of families with the use of the PH increases the rate of treatment failure. 24 , 29 Compared with the PH, the THFS is easier to use and families are more compliant with its use, which helps to explain the high rate of good clinical outcomes. 3 This is why the THFS has gained popularity among paediatric orthopaedic surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…The literature has reported the use of some orthotic devices in treatment of the DDH, such as rigid and semirigid abduction braces, to replace the use of Pavlik harness and the spica cast (Dyskin and Ferrick, 2015;Hedequist et al, 2003;Ibrahim et al, 2013;Uras et al, 2014;Wahlen and Zambelli, 2015;Wilkinson et al, 2002). The use of an abduction brace is easier for the patient, parents and the physician.…”
Section: Introductionmentioning
confidence: 99%